From the Outside-In: The Francisella tularensis Envelope and Virulence - Rowe, Hannah M.; Huntley, Jason F. (Frontiers in Cellular and Infection Microbiology, 2015)
Francisella tularensis is a highly-infectious bacterium that causes the rapid, and often lethal disease, tularemia. Many studies have been performed to identify and characterize the virulence factors that F. tularensis uses to infect a wide variety of hosts and host cell types, evade immune defenses, and induce severe disease and death. This review focuses on the virulence factors that are present in the F. tularensis envelope, including capsule, LPS, outer membrane, periplasm, inner membrane, secretion systems, and various molecules in each of aforementioned sub-compartments. Whereas, no single bacterial molecule or molecular complex single-handedly controls F. tularensis virulence, we review here how diverse bacterial systems work in conjunction to subvert the immune system, attach to and invade host cells, alter phagosome/lysosome maturation pathways, replicate in host cells without being detected, inhibit apoptosis, and induce host cell death for bacterial release and infection of adjacent cells. Given that the F. tularensis envelope is the outermost layer of the bacterium, we highlight herein how many of these molecules directly interact with the host to promote infection and disease. These and future envelope studies are important to advance our collective understanding of F. tularensis virulence mechanisms and offer targets for future vaccine development efforts.